i know this is a simple differentiation, but i just can't remember how to do it!
can someone please differentiate
((x^3)+3(x^2)+1) ^(1/3)
also how can i write x^2 on this forum so it looks like how x^2 should look, with a superscript 2.
Hello, mathmonster!
You need the Chain Rule . . .
$\displaystyle f(x) \;=\;\left(x^3+3x^2+1\right)^{\frac{1}{3}}$
$\displaystyle f'(x)\;=\;\frac{1}{3}\left(x^3+3x^2+1\right)^{-\frac{2}{3}}(3x^2 +\, 6x) \;=\;\frac{3x^2+6x}{3(x^3+3x^2+1)^{\frac{2}{3}}} \;=\;\frac{x^2+2x}{(x^3+3x+1)^{\frac{2}{3}}}$